Pengaruh Penggunaan Audiovisual dalam Pembelajaran Tafsir Al-Qur’an terhadap Pemahaman Siswa Kelas 3 Pesantren Al-Amanah - Maulana Imam Ma’ruf; La Jusu; Madi Madi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to quantitatively test the impact of using audiovisual media in learning Al-Qur'an interpretation on students' understanding. This study was motivated by the low level of students' understanding observed when the interpretation material was delivered through conventional teaching methods. Using a quantitative approach with a quasi-experimental design, this study adopted a pretest-posttest model involving an experimental group and a control group. The sample consisted of 62 students, divided into an experimental group exposed to audiovisual media and a control group taught through traditional lectures. Data collection instruments included questionnaires and comprehension tests given before and after the intervention. The results of the t-test analysis revealed a significant difference between the two groups (p < 0.05), indicating that the use of audiovisual media had a positive and significant effect on improving students' understanding of Al-Qur'an interpretation.